Pitungan and birth variations of first-born among Javanese ethnic population in Indonesia - Lucy Dyah Hendrawati (Faculty of Social and Political Science, Universitas Airlangga, 2021)
There is a phenomenon among the Javanese ethnic population, in which many wedding ceremonies are held whenever the Javanese calendar points to particular months such as Besar, Rejeb, and Ruwah, because marrying in those months is believed to bring good fortune. This study aimed to analyze the influence of wedding date determination through pitungan and feeling safe on birth variations of first-born and the number of children the wife gives birth to. The research was conducted in Blitar City, Blitar Regency, and Surabaya City with 193 married couples. Linear Regression and Chi-square were the statistical tests used in this research. Chi-square and Linear Regression tests proved that pitungan affects the birth variations of first-born (p = 0.004; p = 0.004) and the number of children a couple has (p = 0.007; p = 0.002). Both Chi-square and Linear Regression proved that feeling safe (roso slamet) does not have any significant effect on birth variations of first-born (p = 0.162; p = 0.767) and the number of children in household (p = 0.863; p = 0.680). The conclusion is that there is an important relationship between pitungan and birth variation in which the more pitungan is done, the sooner first-born is given birth to and the more children a married couple has.